Fibrous dysplasia of bone: a clinicopathologic review - Mohan H; Mittal P; Mundi I; Kumar S (Dove Medical Press, 2011)
Harsh Mohan1, Preeti Mittal1, Irneet Mundi1, Sudhir Kumar21Department of Pathology, 2Department of Orthopedics, Government Medical College, Sector 32, Chandigarh, IndiaAbstract: Fibrous dysplasia of the bones is an uncommon congenital skeletal disorder that is found equally in both genders and is not inherited. Its etiology has been linked to an activating mutation of Gsα and the downstream effects of the resultant increase in cAMP. Fibrous dysplasia is categorized as either monostotic or polyostotic, and may occur as a component of McCune-Albright syndrome or the rare Mazabraud syndrome. Long bones, skull bones, and ribs are the most commonly affected bones. The radiological picture is somewhat variable, including a ground-glass appearance, expansion of the bone, and sclerosis surrounding the lesion. Histologically, fibrous dysplasia shows irregularly-shaped trabeculae of immature, woven bone in a background of variably cellular, loosely arranged fibrous stroma. It may be complicated by pathologic fracture, and rarely by malignant transformation. This review examines interesting issues surrounding the etiology of fibrous dysplasia, its clinical and laboratory manifestations, radiological picture, utility of bone biopsy, gross and microscopic pathology, complications, and its differential diagnostic considerations.Keywords: fibrous dysplasia, McCune-Albright syndrome, monostotic form, polyostotic form